PENGAMANAN PESAN MENGGUNAKAN ALGORITMA DATA ENCRYPTION STANDARD (DES) - fahmi ruziq (LPPM Politeknik LP3I Medan, 2021)
Cryptography is an encryption technique, where the data to be encrypted will be encrypted using a key to become data that is difficult to read by other parties who do not have a decryption key. The DES algorithm is a symmetric block cipher cryptographic algorithm that uses a block size of 64 bits and a key size of 56 bits. In this study the DES algorithm will be used to encrypt messages. The result of this research is that the length of the file characters is directly proportional to the encryption and decryption process